Análisis de la exposición al riesgo del Efectivo Generado por la Operación (EGO) bajo incertidumbre macroeconómica y de mercado. (2010)
This paper is a methodology for calculating the EGOaR (Operational Cash Flow at risk) for nonfinancial firms. This proposal seeks to overcome the weaknesses referred to other methods for calculating the CFaR (Cash Flow at Risk) when regard the company as an average of a group of similar competitors and not including exogenous sources of risk in the individual company. In the proposed method does not use the cash flow but the Operational Cash Flow (EGO) as the dependent variable in the exposure model, avoiding punish the historic company cash flow with strategic investments. Another advance is the use of time series theory to estimate and simulate the behavior following exogenous variables that influence the generation of cash in the company.